Institutional amnesia pushes fish spawning aggregations towards extirpation. Issue 2 (2nd March 2023) - Fulton, Stuart
Abstract: How institutions create and manage knowledge has been explored in the context of management and business science. However, little effort has been made to understand how, and why, these institutions forget what works or does not work, and no research in this field has been conducted in conservation or fisheries science. This paper examines the concept of institutional amnesia by focussing a lens on fish spawning aggregations and efforts to monitor and protect them in the Mesoamerican Reef. For over 20 years, underwater visual census survey data has been collected periodically at 36 spawning aggregation sites, and grey literature is available since the 1940's, yet managers and conservation practitioners report that abundance tendencies for 48% of grouper and snapper spawning species across the 36 sites are ' Unknown ', despite measurable >99% declines in fish abundance in some cases. This text examines the reasons why site managers are uncertain in their reporting. The central argument is that institutional amnesia (resulting from factors such as staff turnover, ineffective institutional learning, poor record keeping and a lack of storytelling) is contributing to suboptimal ecological outcomes for spawning aggregations, which are likely to continue unless measures are taken to ensure the continuity of institutional knowledge. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Resumen: Se ha explorado cómo las instituciones crean y gestionan el conocimiento en el contexto de manejo y de ciencias empresariales. Sin embargo, se ha realizado poco esfuerzo para comprender cómo y por qué estas instituciones olvidan lo que funciona o no funciona, y no se ha realizado ninguna investigación en este campo en la conservación o ciencias pesqueras. Este documento examina el concepto de la amnesia institucional, utilizando como ejemplo las agregaciones de desove de peces y los esfuerzos para monitorearlas y protegerlas en el Arrecife Mesoamericano. Durante más de 20 años, los datos de censos visuales submarinos se han recopilado periódicamente en 36 sitios de agregación de desove, y existe literatura gris disponible desde la década de 1940; sin embargo, los manejadores y profesionales de la conservación informan que las tendencias de abundancia para el 48% de las especies de desove de mero y pargo en los 36 sitios son ' Desconocidas ', a pesar de disminuciones medibles de >99% en la abundancia de peces en algunos casos. Este texto examina las razones por las que los manejadores de los sitios tienen incertidumbre sobre los datos reportados. El argumento central es que la amnesia institucional (resultante de factores como la rotación de personal, el aprendizaje institucional ineficaz, el mantenimiento deficiente de registros y la falta de una narrativa histórica) está contribuyendo a resultados ecológicos subóptimos para las agregaciones de desove, que probablemente continúen a menos que se tomen medidas para garantizar la continuidad del conocimiento institucional.